Massenwahntheorie und Friedenspoetik : Hermann Broch und die bedrohte Demokratie des 20. Jahrhunderts - McGaughey, Sarah (2023)
The radical rupture in civilization, the future and defense of democracy, the fight against totalitarianism and mass hysteria, the commitment to human rights, and the utopian potential of literature - these were the topics that occupied the mind of Jewish author, intellectual, and US émigré Hermann Broch (1886-1951). This volume investigates the topicality of his thought in the context of interdisciplinary peace and democracy research.